Smart Home and Smart Farming Prototype Making Training Based on Internet of Things (IOT) at SMA Negeri 3 Pontianak - Hadary, Ferry; Saziati, Ochih; Desmaiani, Herda (Universitas Veteran Bangun Nusantara, 2025)
This Community Service Program (PkM) was carried out at SMA Negeri 3 Pontianak with the aim of providing training to students related to the implementation of Internet of Things (IoT) technology in smart home and smart farming systems. This activity was chosen because most of the Indonesian population does not have an understanding and knowledge of the IoT concept, especially the younger generation of school age. The implementation method includes socialization, training and direct simulation of making IoT-based smart home and smart farming prototypes using ESP8266 sensors as microcontrollers. The PkM activities succeeded in increasing the participants knowledge about IoT. The results of this questionnaire prove the increased understanding of participants from the delivery of material and increased ability to use and develop IoT and increased learning motivation to apply IoT technology in everyday life. This proves the positive impact of the facilitator's involvement on partners, with this training it is hoped that new ideas or ideas will emerge from the younger generation to face the digital era and be able to identify and solve problems around them by utilizing Internet of Things technology. Keywords: Internet of Things (IoT), Smart Home, Smart Farming, SMA Negeri 3 Pontianak